AB0777 Wearable Pulsed Electromagnetic Fields Device in Knee Osteoarthritis Patients: Preliminary Results of A Double Blinded, Randomized, Placebo Controlled, Clinical Trial. (10th June 2014) - Bagnato, G.; Sciortino, D.; Marino, N.; Miceli, G.; Roberts, W.N.; Bagnato, G.
Abstract : Background: Knee osteoarthritis (OA) is the most common form of joint disease and the major cause of pain and physical disability among elderly people. To relieve pain, many patients, in order to avoid long-term complications of conventional therapy, turn toward non-pharmacologic therapies. Among these, pulsed electromagnetic fields (PEMF) therapy, although it has shown promising in vivo results, has controversial clinical benefits in human studies [1]. Objectives: The aim of the study is therefore to evaluate the efficacy of a wearable PEMF device on pain intensity reduction in patients affected by knee osteoarthritis. Secondary aim is to evaluate the effect on stiffness, function, quality of life and pressure pain threshold. Methods: Randomized, double-blind, placebo-controlled clinical trial, with equal randomization (1:1) and parallel group study. Knee OA patients, enrolled according to the ACR criteria, with age >40 years, persistent pain, defined as a minimum mean score of 40 on a 100 mm visual analog scales (VAS), symptomatic disease for at least 6 months prior to enrollment have been recruited to be randomly assigned to wear active (n=20) or placebo (n=20) device for 12 hours daily for 4 weeks. Patients affected by secondary causes of OA or by diabetes mellitus have been excluded. The primary outcome measure was score improvement from baseline to 1 months posttreatment in VAS and in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), as recommended by the Outcome Measures in Rheumatology Clinical Trials group [2]. In addition, quality of life, evaluated through the 36-item Medical Outcomes Study Short-Form 36 version 2 (SF-36 v.2) and pressure pain threshold measured through a pressure algometer applied on the anterior part of the thigh (PPT-THI) and on the distal interphalangeal joint (PPT-DIPJ) have been measured. Trial registration number: NCT01877278 Results: Baseline data of placebo and active groups were not significantly different. In the active group, after 4 weeks of treatment, T-test results showed a significant improvement of VAS pain (p<0.005), WOMAC pain (p<0.001), WOMAC function (p<0.02) and WOMAC stiffness (p<0.02). Quality of life, as expressed by SF-36 physical and mental health scores, improved in patients in active therapy after 4 weeks (p<0.04). Both pressure pain threshold scores significantly increased after 4 weeeks in patients treated with the active device (PPT-DIPJ p<0.05, PPT-THI p<0.001). No statistically significant changes have been evidenced in the placebo group. No adverse events have been observed during the study. Conclusions: Wearable PEMF therapy, given the low risk of adverse events, appears to be a promising and effective therapy in reducing pain intensity, modulating pain threshold and increasing quality of life in OA patients. Larger human studies are needed to confirm the long-term effect on pain intensity and on the modulation of pain threshold. References: Ryang We S et al. Effects of pulsed electromagnetic field on knee osteoarthritis: a systematic review. Rheumatology (Oxford). 2013 May;52(5):815-24 Bellamy N et al. Recommendations for a core set of outcome measures for future phase III clinical trials in knee, hip and hand osteoarthritis. Consensus development at OMERACT III J Rheumatol 1997;24: 799–802 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6015